Activation of Cannabinoid Type Two Receptors (CB(2)) Diminish Inflammatory Responses in Macrophages and Brain Endothelium - Persidsky, Yuri (J Neuroimmune Pharmacol, 2015)
Chronic neuroinflammatory disorders (such as HIV associated neurodegeneration) require treatment that decreases production of inflammatory factors by activated microglia and macrophages and protection of blood brain barrier (BBB) injury secondary to activation of brain endothelium. Cannabioid type 2 receptor (CB(2)) is highly expressed on macrophages and brain microvasular enndothelial cells (BMVEC) and is upregulated in inflammation and HIV infection. It has been shown that CB(2) activation dampened inflammatory responses in macrophages and BMVEC. In this study, we assessed by PCR array the expression of a wide range of genes increased in macrophages and BMVEC in inflammation. TNFα treatment upregulated 33 genes in primary human BMVEC, and two highly selective CB(2) agonists diminished expression of 31 and 32 genes. These results were confirmed by functional assays (BBB protection after inflammatory insult and decreased migration of monocytes across BMVEC monolayers after CB(2) stimulation). Similarly, CB(2) stimulation in primary human macrophages led to the suppression of 35 genes out of the 50 genes upregulated by LPS. Such changes in gene expression paralleled diminished secretion of proinflammatory factors. These results indicate the potential utility of CB(2) agonists for the treatment of neuroinflammation.